Novel diastereomeric ionone derivatives from Altemanthera sessilis (Linn.) R.Br. - Tremor, Noemi M. (Animo Repository, 2001)
The chloroform extract of the dried leaves of Altemanthera sessilis (Linn.) R. Br. afforded a mixture of diastereomers of new ionone derivatives whose structure were elucidated by extensive 1D and 2D NMR spectroscopy and mass spectrometry. Oxidative cleavage of the mixture to aldehyde with manganese dioxide confirmed diastereomerism arose from a racemic side chain chiral centre. Antimicrobial tests on the mixture of diastereomers and derivative indicated that they have low activities against Pseudomonas aeruginosa and Trichophyton mentagrophytes.